Desecuritization and Securitization of Drug Trafficking within the Framework of the Peace Agreement in Colombia - Guerra-Molina, Rene-Alonso; Badillo-Sarmiento, Reynell (FLACSO - Sede Ecuador, 2021)
The article analyzes the process of de-securitization and securitization of drug trafficking in Colombia and the influence of the Peace Agreement between the Colombian government and the Revolutionary Armed Forces of Colombia (FARC-EP) on this process. To this end, the concept of “securitization”, developed by the Copenhagen School, is used as a theoretical approach. Through the Political Discourse Analysis (PDA) method, the speech acts of the administrations of Santos and Duque are analyzed, in order to identify the justifications for the decisions they made and changes in their approach to the fight against illicit drugs. It is concluded that the Peace Agreement was an attempt to de-securitize the strategy to fight drug trafficking in Colombia, given that it highlighted the political dimension of that illegal market and urged the State to promote a comprehensive solution beyond the military strategy and the threat to national security.